RISK IDENTIFICATION AND MITIGATION STRATEGIES FOR WORKERS IN VEHICLE WASHING OPERATIONS - Fikrihadi Kurnia; Cinta Mugia Wening Galih; Ade Febrian (Energy, Materials and Product Design, 2025)
This study identifies and evaluates occupational health and safety risks faced by workers in vehicle washing operations in Mataram, Nusa Tenggara Barat, focusing on motorcycle and car wash services. Through observational studies conducted on April 6, 2025, key hazards were identified, including musculoskeletal disorders (MSDs) from non-ergonomic postures, chemical exposure from soap, slipping on wet floors, and noise from compressors. The Rapid Entire Body Assessment (REBA) method revealed high ergonomic risks, with REBA scores of 10 for both motorcycle and car wash workers, indicating a significant risk of MSDs due to prolonged bending and repetitive motions. Bowtie Analysis further mapped causes, consequences, and control measures, emphasizing non-ergonomic postures and chemical hazards as primary concerns. Preventive strategies, such as ergonomic training, long-handled tools, and personal protective equipment (PPE), were proposed to mitigate risks. The findings align with global studies reporting high MSD prevalence among sanitation workers, underscoring the need for ergonomic interventions and safety protocols. This study contributes to the literature by offering tailored risk mitigation strategies for the vehicle washing industry, advocating for enhanced worker safety, improved productivity, and reduced occupational health risks through comprehensive risk management and ergonomic solutions..